PENGARUH KEKUATAN PASAR TERHADAP KECUKUPAN MODAL PADA BANK KONVENSIONAL DAN SYARIAH DI INDONESIA - Yussi Ananda; Hasdi Aimon; Dewi Zaini Putri (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to find out how the Influence of Market Power on Capital Adequacy in Conventional and Islamic Banks in Indonesia in the long and short term. The data used are secondary data in the form of time series from 2006: Q1 to 2016: Q4, with documentation data collection techniques and library studies obtained from relevant institutions and agencies. The variables used are Market Power, Deposits, Capital, Inflation and Economic Growth. The research methods used are: (1) Error Correction Model (ECM) Analysis, (2) Classical Assumption Test. The results of the study show that (1) Short-term paths of Conventional Bank Market Power are higher than Islamic banks. This means that in the short term the Konvensionsal Bank dominates the banking market in Indonesia. While in the long run Market Power in Islamic Banks is higher than Conventional Banks. So Islamic banks in the long run dominate the banking market in Indonesia. (2) In the short term and long term deposits at Conventional Banks are higher compared to Islamic Banks. So conventional banks in the short and long term can collect more banking funds in Indonesia. (3) In the short and long term capital in Islamic banks is higher than conventional banks. So Islamic banks in the short and long term dominate banking capital in Indonesia. (4) In the short and long term, inflation in conventional banks is higher compared to Islamic banks. So it can be said that conventional banks in the short and long term are influenced by inflationary shocks in Indonesia. (5) In the short-term and long-term economic growth in Islamic banks is higher than conventional banks. So it can be said that Islamic banks in the short and long term are influenced by the high and low level of Indonesia's economic growth.Keywords: Market Power, Capital Adequacy, Conventional and IslamicBanks, and Error Correction Model (ECM).